Heat endurance and impact resistance: Investigating fibrous engineered cementitious composites under impact loads at elevated temperatures - Abid S.R.; Al-Ameri R.A.; Murali G.; Ali S.H.; zaka M. (Elsevier Ltd, 2025)
This study presents experimental findings that assess the influence of boundary end conditions on the response of engineered cementitious composites (ECC) reinforced plates under impact loading, both before and after exposure to elevated temperatures. Testing encompassed three sets of small-sized ECC plates alongside three comparable sets of normal-strength concrete (NC) plates. The distinguishing factor among the three groups lies in the end boundary conditions. Specimens were tested under different scenarios, including four-end restriction, two-end restriction, and a clamped case. Within each group, three plate specimens underwent heating to temperatures of 200, 400, and 600 C, while the fourth plate specimen served as an unheated reference for comparison. In total, 24 specimens were subjected to repeated drop-weight impacts until failure. The study recorded key parameters for each plate, including impact force, central deflection, and acceleration for each impact blow. In addition, the number of blows that caused failure (Nf) was recorded for each plate. The test results revealed that exposure to elevated temperatures led to decreased Nf and impact force for both NC and ECC plates, concurrently with increased deflection. A semi-stabilized region between 200 and 400 C was identified in the relationships between the Nf and temperature, where Nf records decreased by up to 62 % and 77 % for NC, and 85 % and 91 % for ECC after exposure to 200 and 400 C, respectively. However, the impact resistance significantly diminished for plates exposed to 600 C, exhibiting minimal Nf records, reduced impact forces, and high deflections. In the case of unheated plates, the augmentation of the end restriction resulted in an increase in the retained impact force and a decrease in deflection. However, a discernible trend was not observed for heated plates, mainly attributable to the thermal degradation affecting the corners of the restrained edges in some plates. ? 2024 The Authors